English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

integral of (lnx)/((x^(3/2))

I tried let u= lnx and x^(3/2) and it didn't work.

2007-07-16 10:26:14 · 3 answers · asked by jessica y 1 in Science & Mathematics Mathematics

3 answers

How about letting t = x^(-1/2)
dt = -1/2 * x^(-3/2) * dx

So integral of lnx * x^(-3/2) * dx
= -2 * ln(1/t^2) * dt
= -2 * ln[t^-2] * dt
= 4*lnt*dt

Now you can integrate by parts using
u = ln(t), dv = 4
du = dt/t, v = 4t

integral = 4t*ln(t) - integral of 4*dt
= 4*t*[ln(t) - 1]
= 4/sqrt(x) * [ln(x^-1/2) - 1]
= 4 * [-1/2 * lnx - 1] / sqrt(x)
= -2 * [lnx - 2 ] / sqrt(x)

2007-07-16 10:33:39 · answer #1 · answered by Dr D 7 · 0 0

Hello

[(1/x)*(x^(3/2)) - (3/2)x^(1/2)*lnx]/x^3
You will need to simply this.
Hope This Helps!

2007-07-16 17:32:07 · answer #2 · answered by CipherMan 5 · 0 0

why, it shoud:

u = ln x
x = exp(u)

int of (lnx) / x^3/2 dx =
int of u / exp(u)^3/2 d[exp(u)] =
int of u / exp(u)^3/2 exp(u) du =
int of u / exp(u)^1/2 du =
int of u exp(-u/2) du =

-2 int of u d[exp(-u/2)] =

by part:
-2( u exp(-u/2) - int of exp(-u/2) du) =
-2(u exp(-u/2) + 2 exp(-u/2)) + C=
(4 -2u)exp(-u/2) + C=
(4 -2ln x)exp(-ln x/2) + C
(4 -2ln x)/√exp(ln x) + C
(4 -2ln x)/√x + C

2007-07-16 17:36:19 · answer #3 · answered by Alexander 6 · 0 0

fedest.com, questions and answers